PATTERNS OF STEROID USE AMONG A REAL-WORLD NATIONAL COHORT OF VETERANS WITH INFLAMMATORY BOWEL DISEASE. (26th January 2023) - Pham, Codey; Xu, Anthony; Sansgiry, Shubhada; Waljee, Akbar; Hou, Jason
Abstract: BACKGROUND: Corticosteroids are effective in the acute improvement of symptoms in inflammatory bowel disease (IBD) but are not recommended as maintenance therapy due to lack of long-term efficacy and significant adverse effects. Long term goals for medical management in IBD include achieving steroid-free remission. Biologics such as the anti-tumor necrosis factor alpha Infliximab (IFX) are used to achieve clinical remission, however patterns of continued steroid use among patients on maintenance IFX have not been fully studied. The aim of this study is to evaluate patterns of concomitant steroid use in individuals with IBD on maintenance IFX. METHODS: We performed a retrospective cohort study using the national Veteran's Health Administration dataset. Patients with IBD were identified using a previously validated algorithm of ICD9/10 codes and confirmed by manual chart review. Dispensed medications and demographic data were obtained from VA Corporate Data Warehouse. Patients were eligible for inclusion if they had a confirmed diagnosis of IBD and on maintenance IFX. Maintenance IFX- index date was defined as the first dose of IFX in 2017 with receipt of IFX 7 to 9 weeks before and after IFX-index date. The study period for steroid use was six months prior to and following the IFX-index date. Continued steroid use was defined as two or more filled prescription of oral steroids during the study period. RESULTS: There were 642 individuals included who met the criteria outlined above. The majority (594, 92.5%) were male. The racial breakdown was as follows: 516 (80.3%) White, 85 (13.3%) Black, 18 (2.8%) other races, and 23 (3.6%) with unknown race. A total of 402 individuals (62.6%) had ulcerative colitis, 240 individuals (37.4%) had Crohn's disease. The average age at the IFX-index date was 46.8 (±15.8) years. The average time from initial date of IFX exposure to the Maintenance IFX-index date was 3.6 years. During the study period, 198 (30.9%) patients filled at least one prescription for steroids. 145 of the 198 (73.2%) individuals prescribed had continued steroid use with two or more filled steroid prescriptions, with an average of 3.9 filled prescriptions of steroids during the study period. CONCLUSION: While IFX has been shown to be effective in the induction and maintenance of remission in IBD, we observe high rates of continued steroid use in a national cohort of patients with IBD on maintenance IFX. Continued steroid use in patients on IFX maintenance implies inadequate IBD control despite IFX. Further study is required to understand reasons for continued steroid use in order to improve rates of steroid-free remission in IBD.